Loneliness Promotes Inflammation During Acute Stress - Jaremka, Lisa M.; Fagundes, Christopher P.; Peng, Juan; Bennett, Jeanette M.; Glaser, Ronald; Malarkey, William B.; Kiecolt-Glaser, Janice K. (Psychological Science, 2013)
Although evidence suggests that loneliness may increase risk for health problems, the mechanisms responsible are not well understood. Immune dysregulation is one potential pathway: Elevated proinflammatory cytokines such as interleukin-6 (IL-6) increase risk for health problems. In our first study ( N = 134), lonelier healthy adults exposed to acute stress exhibited greater synthesis of tumor necrosis factor-alpha (TNF-α) and IL-6 by peripheral blood mononuclear cells (PBMCs) stimulated with lipopolysaccharide (LPS) than their less lonely counterparts. Similarly, in the second study ( N = 144), lonelier posttreatment breast-cancer survivors exposed to acute stress exhibited greater synthesis of IL-6 and interleukin-1 beta (IL-1β) by LPS-stimulated PBMCs than their counterparts who felt more socially connected. However, loneliness was unrelated to TNF-α in Study 2, although the result was in the expected direction. Thus, two different populations demonstrated that lonelier participants had more stimulated cytokine production in response to stress than less lonely participants, which reflects a proinflammatory phenotype. These data provide a glimpse into the pathways through which loneliness may affect health.